2011
DOI: 10.1051/0004-6361/201015602
|View full text |Cite
|
Sign up to set email alerts
|

The Galactic unclassified B[e] star HD 50138

Abstract: Context. HD 50138 is a southern star that presents the B[e] phenomenon, but its evolutionary stage is still not well known. This object presents spectral variability, which can be explained by outbursts or shell phases. Spectropolarimetric observations have shown the presence of a non-spherically symmetric circumstellar environment that is responsible for the B[e] phenomenon. However, up to now, the structure of the circumstellar medium of this object has not been studied deeply. Aims. Based on recent optical … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
33
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 26 publications
(32 reference statements)
9
33
0
Order By: Relevance
“…They are closed to the images get by reconstruction. The results are also consistent with that found with previous observations 19,27 . The authors found similar P.A.…”
Section: Parametric Fitsupporting
confidence: 94%
See 1 more Smart Citation
“…They are closed to the images get by reconstruction. The results are also consistent with that found with previous observations 19,27 . The authors found similar P.A.…”
Section: Parametric Fitsupporting
confidence: 94%
“…They are useful to analyze MWC158 (also known as HD50138). This star is a Be star known to have the B[e] phenomenon and presents a strong variability [14][15][16][17] which complexify the evolutionary stage identification of the source. Its distance is poorly constrain (d = 500pc ± 150pc 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…5 of Borges Fernandes et al 2011). First believed to be quality (...) clearly lower compared to the K-band data (Borges Fernandes et al 2011), the increase of the visibilities of the H-band data has been observed not only on VLTI/AMBER, but also with A&A 564, A80 (2014) VLTI/PIONIER. This indication caused us to consider an astrophysical interpretation: the change of visibility is generated by the different chromatic behavior between the central star that peaks in the visible and the circumstellar material that radiates out mainly in the NIR (Kluska et al 2012).…”
Section: Introductionmentioning
confidence: 95%
“…Subsequent observations (Miroshnichenko et al , 2009(Miroshnichenko et al , 2011aBorges Fernandes et al 2009Rodríguez et al 2012;Polster et al 2012;Liermann et al 2014) and modeling (Carciofi et al 2010;Borges Fernandes et al 2011) of FS CMa stars have not been capable of unraveling the enigmatic nature of these objects. One of the most puzzling issues refers to the observationally inferred mass-loss rates, which are 2-3 dex higher than predicted by wind theory for B-type main-sequence stars.…”
Section: Introductionmentioning
confidence: 99%